The Historical Works of al-Thabari, Ibn al-Atsir, and al-Kala’i in Comparative Analysis - Rofiq, Ahmad Choirul (Historia Madania: Jurnal Ilmu Sejarah, 2023)
Al-Thabari, Ibn al-Atsir, and al-Kala’i were undoubtedly scholarly historians of Islamic history. This paper uses the historical method to analyze the works of al-Thabari, Ibn al-Atsir, and al-Kala’i relating to Hurub al-Riddah and the problem of applying the death penalty to apostates. It is concluded that they didn’t provide adequate historical explanations and the causal factors of Hurub al-Riddah, although the political factors primarily drove Hurub al-Riddah. The differences of their works were only in 'small' things, such as differences in the mention of the names of the perpetrators of events and differences in sentences. It is not easy to determine which work is more comprehensive. It may be more appropriate to combine many historical sources to comprehend the history of Hurub al-Riddah. The readers of their works are encouraged to analyze their descriptions critically and seek historical explanations through other references written by critical historians. The meaning of riddah at that time did not refer solely to everyone who renounced the Islam religion but also to those who rebelled against the Islamic government. Therefore, the essence of riddah wars was not in conflict with freedom of faith in Islam.